2018
DOI: 10.3892/mmr.2018.9609
|View full text |Cite
|
Sign up to set email alerts
|

Long noncoding RNA TSLNC8 suppresses cell proliferation and metastasis and promotes cell apoptosis in human glioma

Abstract: Glioma is among the most common primary brain tumors and one of the most aggressive and lethal forms of human cancer. Long noncoding RNAs (lncRNAs) have demonstrated great importance in the development and progression of cancer. The present study aimed to investigate the role of the novel tumor suppressive lncRNA on Chromosome 8p12 (TSLNC8), in cell proliferation, metastasis and apoptosis in human glioma. It was initially reported that the relative transcript levels of TSLNC8 were significantly decreased in hu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 32 publications
1
13
0
Order By: Relevance
“…Our study showed that TSLNC8 was downregulated in glioma tissues and cells. TSLNC8 overexpression significantly inhibited the viability, migration and invasion of glioma cells and promoted glioma cell apoptosis, indicating that TSLNC8 acts as a tumour suppressor in glioma cells, which is consistent with the findings reported by Chen and Yu in their study [18]. However, our findings further revealed the mechanism by which TSLNC8 regulates the biological behaviour of glioma cells.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Our study showed that TSLNC8 was downregulated in glioma tissues and cells. TSLNC8 overexpression significantly inhibited the viability, migration and invasion of glioma cells and promoted glioma cell apoptosis, indicating that TSLNC8 acts as a tumour suppressor in glioma cells, which is consistent with the findings reported by Chen and Yu in their study [18]. However, our findings further revealed the mechanism by which TSLNC8 regulates the biological behaviour of glioma cells.…”
Section: Discussionsupporting
confidence: 93%
“…It has been reported that TSLNC8 acts as a tumour suppressor and is involved in the regulation of various malignant tumour diseases, including hepatocellular carcinoma [15], breast cancer [16] and non-small cell lung cancer [17]. Additionally, existing studies have shown that TSLNC8 suppresses cell proliferation and metastasis and promotes cell apoptosis in human glioma [18]. However, the detailed function of TSLNC8 in glioma remains largely unknown.…”
Section: Introductionmentioning
confidence: 99%
“…TSLNC8 was rstly found to be downregulated in hepatocellular carcinoma (HCC) tissues and signi cantly suppress the proliferation and metastasis of HCC cells by competitively interacting with transketolase and STAT3 and inactivating IL-6/STAT3 pathway (11). Downregulation of TSLNC8 expression was also observed in breast cancer, glioma, and non-small cell lung cancer (12)(13)(14). However, the functional role and molecular mechanism of TSLNC8 in PC progression remain to be elucidated.…”
Section: Introductionmentioning
confidence: 99%
“…Tumor-suppressive lncRNA on chromosome 8p12 (TSLNC8), also named LINC00589, is one of various lncRNAs [17]. TSLNC8 was reported to be remarkably downregulated in human glioma tissues, suppressing proliferation and facilitating apoptosis in human glioma cells [18]. Furthermore, TSLNC8 exerts its tumor-suppressive function by inactivating the IL-6/STAT3 signaling pathway in liver cancer [17].…”
Section: Introductionmentioning
confidence: 99%